2009
DOI: 10.2353/ajpath.2009.080352
|View full text |Cite
|
Sign up to set email alerts
|

SV40-Induced Expression of Calretinin Protects Mesothelial Cells from Asbestos Cytotoxicity and May Be a Key Factor Contributing to Mesothelioma Pathogenesis

Abstract: The calcium-binding protein calretinin has emerged as a useful marker for the identification of mesotheliomas of the epithelioid and mixed types, but its putative role in tumor development has not been addressed previously. Although exposure to asbestos fibers is considered the main cause of mesothelioma, undoubtedly, not all mesothelioma patients have a history of asbestos exposure. The question as to whether the SV40 virus is involved as a possible co-factor is still highly debated. Here we show that increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 62 publications
(71 reference statements)
1
34
0
Order By: Relevance
“…Contrasting reports have appeared in the literature on the presence of SV40 footprints in humans and its association with human tumors (20)(21)(22). SV40 antibody detection had been attempted in several studies using serologic methods with SV40 virus-like particles (VLPs), but because of high protein homology among the three main polyomaviruses SV40, BKV, and JCV, the results were always affected by some cross-reactivity (23)(24)(25)(26)(27)(28)(29)(30).…”
mentioning
confidence: 76%
“…Contrasting reports have appeared in the literature on the presence of SV40 footprints in humans and its association with human tumors (20)(21)(22). SV40 antibody detection had been attempted in several studies using serologic methods with SV40 virus-like particles (VLPs), but because of high protein homology among the three main polyomaviruses SV40, BKV, and JCV, the results were always affected by some cross-reactivity (23)(24)(25)(26)(27)(28)(29)(30).…”
mentioning
confidence: 76%
“…Mutations in either BRE 5 or BRE 6 reduced the repressor effect by approximately 50% each indicating that both elements contribute to the butyrate-induced repression of CR expression. Since aberrant expression of CR is also the hallmark of mesotheliomas, in particular of the epithelial type, we used either the SV40-immortalized cell line MeT-5A or the mesothelioma cell line ZL34 that both express CR [Henzi et al, 2009] and [Saydan et al, 2001], respectively. Unlike in colon cancer cells, where butyrate mainly affects proliferation, doses of >1 mM led to massive death of cells of mesothelial origin starting from the third day of butyrate treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The question as to whether the SV40 virus is involved as a possible cofactor is still highly debated. Henzi et al [41] have shown that increased expression of SV40 early gene products in the mesothelial cell line MeT-5A induces the expression of calretinin and that elevated calretinin levels strongly correlate with increased resistance to asbestos cytotoxicity. Calretinin alone contributes significantly to this protective effect because cells stably transfected with calretinin cDNA were shown to be more resistant to the toxic effects of crocidolite than mock-transfected control cells.…”
Section: Primary Tumor Of the Peritoneummentioning
confidence: 99%